Applying FSSAM for Currency Rates Forecasting - Georgieva, Penka Valkova (Transactions on Engineering and Computing Sciences, 2016)
Currency rates forecasting in real-time is a milestone in the process of financial decision making. Assessing the historical performance of currency rates is a major concept in ﬁnancial management. In this paper Fuzzy Software System for Asset Management (FSSAM) is briefly described. This system is applied on real data of currency rates and some of the results are shown.